Signal Tracking and Acquisition Model for Handoff Process in 4G Network - Okorogu, V. N.; Okafor, C. S.; Ezeagwu, C. O. (European Journal of Science, Innovation and Technology, 2023)
Since network providers must adhere to the Quality of Service (QoS) standard when delivering network services to customers, the focus of this paper is on the development of signal tracking and acquisition models in 4G networks. The Nigerian Communication Commission (NCC) being the regulatory body established some key performance indicators (KPIs) that the network providers must follow in order to determine whether the implemented model will increase mobility and handoff management as well as improve QoS delivery. Within the Base Station (BS) footprint for the one week of Drive Tests, where measurements were made at intervals of 600m radii, the Received Signal Strength (RSSI) in the characterized 4G network demonstrated strong signals in the range of -50dBm to -80dBm. Mathematical calculations using the field experimental data collected and MATLAB SIMULINK show full agreement with NCC benchmark. The Call Drop Rate (CDR) is 14% while NCC benchmark is 20%. The Grade of Service (GoS) is 1.5%, which is in line with the NCC guideline of 1% to 2%. The proposed model’s Handoff Success Rate (HOSR) is 91.2%; the NCC benchmark is 80%.